Reproductive allometry of Podocnemis expansa (Testudines: Podocnemididae) in southern Brazilian Amazon - Costa Gonçalves Portelinha, Thiago (2013)
Podocnemis expansa is the largest freshwater turtle in South America and exhibits a complex reproductive behavior. Females lay eggs in sandy banks formed during the dry season. Nesting habitat can influence hatching success and sex determination. In some turtle species, female body size is crucial to determine reproductive parameters such as clutch size and shape. In this study, we investigate allometric relationships between female body size and their tracks, and clutch characteristics and nest shape in sandy beaches along the Javaés River, southern Brazilian Amazon. Our results indicate that female body size can be estimated based on tracks. Larger females leave larger foot tracks in the sand and have larger clutch sizes with larger clutch mass than smaller females. Female carapace width and body mass can be considered reliable variables to estimate clutch size and total clutch mass for the species. Larger females should be protected because they can be responsible for most annual clutch production.